HEPA filtration intervention in classrooms may improve some students' asthma. (4th March 2023) - Vesper, Stephen J.; Wymer, Larry; Coull, Brent A.; Koutrakis, Petros; Cunningham, Amparito; Petty, Carter R.; Metwali, Nervana; Sheehan, William J.; Gaffin, Jonathan M.; Permaul, Perdita; Lai, Peggy S.; Bartnikas, Lisa M.; et al.
Abstract: Objective: The School Inner-City Asthma Intervention Study 2 (SICAS 2) tested interventions to reduce exposures in classrooms of students with asthma. The objective of this post-hoc analysis was limited to evaluating the effect of high-efficiency particulate (HEPA) filtration interventions on mold levels as quantified using the Environmental Relative Moldiness Index (ERMI) and the possible improvement in the students' asthma, as quantified by spirometry testing. Methods: Pre-intervention dust samples were collected at the beginning of the school year from classrooms and corresponding homes of students with asthma ( n = 150). Follow-up dust samples were collected in the classrooms at the end of the HEPA or Sham intervention. For each dust sample, ERMI values and the Group 1 and Group 2 mold levels (components of the ERMI metric) were quantified. In addition, each student's lung function was evaluated by spirometry testing, specifically the percentage predicted forced expiratory volume at 1 sec (FEV1%), before and at the end of the intervention. Results: For those students with a higher Group 1 mold level in their pre-intervention classroom than home ( n = 94), the FEV1% results for those students was significantly ( p < 0.05) inversely correlated with the Group 1 level in their classrooms. After the HEPA intervention, the average Group 1 and ERMI values were significantly lowered, and the average FEV1% test results significantly increased by an average of 4.22% for students in HEPA compared to Sham classrooms. Conclusions: HEPA intervention in classrooms reduced Group 1 and ERMI values, which corresponded to improvements in the students' FEV1% test results.